Insights into the molecular evolution of HslU ATPase through biochemical and mutational analyses. - Kwang Hoon Sung; Hyun Kyu Song (PLoS ONE, 2014)
The ATP-dependent HslVU complexes are found in all three biological kingdoms. A single HslV protease exists in each species of prokaryotes, archaea, and eukaryotes, but two HslUs (HslU1 and HslU2) are present in the mitochondria of eukaryotes. Previously, a tyrosine residue at the C-terminal tail of HslU2 has been identified as a key determinant of HslV activation in Trypanosoma brucei and a phenylalanine at the equivalent position to E. coli HslU is found in T. brucei HslU1. Unexpectedly, we found that an F441Y mutation in HslU enhanced the peptidase and caseinolytic activity of HslV in E. coli but it showed partially reduced ATPase and SulA degradation activity. Previously, only the C-terminal tail of HslU has been the focus of HslV activation studies. However, the Pro315 residue interacting with Phe441 in free HslU has also been found to be critical for HslV activation. Hence, our current biochemical analyses explore the importance of the loop region just before Pro315 for HslVU complex functionality. The proline and phenylalanine pair in prokaryotic HslU was replaced with the threonine and tyrosine pair from the functional eukaryotic HslU2. Sequence comparisons between multiple HslUs from three different biological kingdoms in combination with biochemical analysis of E. coli mutants have uncovered important new insights into the molecular evolutionary pathway of HslU.